(untitled) (Jurnal Bahasa, 2004)
This research has been carried out in a national primary school and the subjects are Malay pupils in level two. Dyslexia Syndrome Theory by Levinson (1994) is applied in this research. The result shows that most of the pupils included in this research can be classified under the category of visual dyslexia or auditory dyslexia. Visual dyslexics face difficulty in learning through visualizing objects because of their inability to retain the image of a word holistically. It is more appropriate to expose them to the phonetic analysis approach while learning reading. An auditory dyslexics experience difficulty in observing hearing. Therefore, they are weak in perceiving and memorizing. The visual approach in learning reading need to be applied to them. There are several methods of learning reading which are suitable for dyslexic pupils in Malaysia such as Orton-Gillingham method, remedial for reverse letters, and remedial for inverse letters. These methods possessed their own techniques.